A Case of “Refractory” Neuropsychiatric Lupus Responsive to Anticoagulation - Rui Wu; Sun Hu (Case Reports in Neurological Medicine)
Neuropsychiatric disorder is a severe complication in 14% to 75% of systemic lupus erythematosus (SLE) patients, which can result in significant morbidity. A 15-year-old female SLE patient with coexistence of dural sinus thrombosis and intracerebral hemorrhage resistant to two pulses of high dose of glucocorticoid was treated with anticoagulation of the low-molecular-weight [LMW] heparin subcutaneously followed by warfarin. The patient demonstrated a remarkable clinical response.